PENGARUH LEVERAGE, BETA, MARKET TO BOOK VALUE RATIO DAN FIRMSIZE TERHADAP EARNIGS RESPONSE COEFFICIENT (ERC) (STUDI PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI 2013-2015) - Roni Roni (e_Jurnal Ilmiah Riset Akuntansi, 2017)
The financial report is a useful information tool for the internal and external parties. Profit is one part of the financial statements that are getting a lot of attention and a lot of research to prove the existence of the relationship very closely with the level of return the company's stock. A quantity that indicates the relationship between profit and the return of shares called the Earnings Response's (ERC). This research aims to know the influence of Leverage, Beta, Market to Book Value Ratio and Firmsize against Earnings Response's (ERC). This research uses the population of manufacturing companies listed on the Indonesia stock exchange (idx) 2013 period up to 2015 in accordance with the specified criteria. The data used in this research is secondary data. Analysis tools are used multiple linear regression and hypothesis testing is performed using a test f, t test and coefficient of determination. The independent variable in this study is Leverage, Beta, Market to Book Value Ratio and Firmsize. While the dependent variable in this study is the Earnings Response's (ERC). Based on the results of data analysis can put forward some conclusions as follows: 1 t test) results show that for Leverage variable have no effect significantly to Earnings Response's (ERC). 2 Variable Beta) do not affect significantly to Earnings Response's (ERC). 3) Market to Book Value Ratio has influence that sigifikan against Earnings Response's (ERC). And Firmsize variables have significant effects against Earnings Response's (ERC).